The Endogenous Hallucinogen and Trace Amine N,N-Dimethyltryptamine (DMT) Displays Potent Protective Effects against Hypoxia via Sigma-1 Receptor Activation in Human Primary iPSC-Derived Cortical Neurons and Microglia-Like Immune Cells - Szabo, Attila; Kovacs, Attila; Riba, Jordi; Djurovic, Srdjan; Rajnavolgyi, Eva; Frecska, Ede (Frontiers in Neuroscience, 2016)
N,N-dimethyltryptamine (DMT) is a potent endogenous hallucinogen present in the brain of humans and other mammals. Despite extensive research, its physiological role remains largely unknown. Recently, DMT has been found to activate the sigma-1 receptor (Sig-1R), an intracellular chaperone fulfilling an interface role between the endoplasmic reticulum (ER) and mitochondria. It ensures the correct transmission of ER stress into the nucleus resulting in the enhanced production of antistress and antioxidant proteins. Due to this function, the activation of Sig-1R can mitigate the outcome of hypoxia or oxidative stress. In this paper we aimed to test the hypothesis that DMT plays a neuroprotective role in the brain by activating the Sig-1R. We tested whether DMT can mitigate hypoxic stress in in vitro cultured human cortical neurons (derived from induced pluripotent stem cells), and in monocyte-derived macrophages and dendritic cells. Here we report that DMT robustly increases the survival of these cell types in severe hypoxia (0.5% O2) through the Sig-1R. Furthermore, this phenomenon is associated with the decreased expression and function of the alpha subunit of the hypoxia-inducible factor 1 (HIF-1) suggesting that DMT-mediated Sig-1R activation may alleviate hypoxia-induced cellular stress and increase survival in a HIF-1-independent manner. Our results reveal a novel and important role of DMT in human cellular physiology. We postulate that this compound may be endogenously generated in situations of stress, ameliorating the adverse effects of hypoxic/ischemic insult to the brain.